Towards Green Supply Chain - For Branston Ltd,Lincolnshire,UK - VRN, Navinan (2010)
Climatic Change is the most important issues that we face globally. This is due to the carbon emissions across the world. Food industry is claimed as one of the Carbon intensive sector. This has made many of the players in the industry to take actions to reduce their carbon footprint through their Green programs. Branston is one of the leading potato suppliers in UK. They are in full swing to reduce their carbon emissions with the help of industry’s best technologies. Through the initial meetings with Mr.Simon Telfer (Logistics Director), my assignment was focused around provision of recommendations to Branston, which can reduce their carbon footprint. Later it was narrowed down to ‘Logistics’. The research, fact findings and recommendations are focused specifically around ‘Green Logistics’. Interview, field analysis and desktop research were done to collect data and identify tools from literature. After careful analysis with the data available, a range of low carbon technologies are recommended for reducing the Carbon footprint. A three step approach has been followed in the recommendations section. 1.Technology Identification: This stage deals with the identification of Low carbon technologies available in the market. 2.Feasibility Analysis: This deals with the feasibility analysis of the low carbon technologies identified, which includes fuel consumption reduction, environmental and technology costs, technology limitations and maturity. 3.Technology Summary: The last stage provides a summary table of the benefits, costs and the applicability of the identified technologies. In conclusion, the report ends by recognizing that low carbon technologies are challenging but yet rewarding. It lies in the hands of Branston to select the most suitable technology and implement them in their vehicles, thereby saving Fuel costs and as well as the Carbon emissions.